Parasite Communities of Icefish (Chionodraco hamatus) in the Ross Sea (Antarctica): Influence of the Host Sex on the Helminth Infracommunity Structure - Mario Santoro; Paolo Cipriani; Bruno Bellisario; Roberta Cimmaruta; Giuseppe Nascetti; MATTIUCCI, Simonetta; ROMANELLI, Francesco (PLoS ONE, 2014)
Parasite communities of Chionodraco hamatus were investigated from Terra Nova Bay (Ross Sea, Antarctica) during host spawning time. Special attention was given to helminth infracommunities and effect of host sex on its structure. A total of 21 taxa including 5 ecto-parasites and 16 endo-parasites were identified. The number of ecto and endo-parasite species per individual host ranged from 1 to 3 and 3 to 10, respectively, while the mean numbers of parasite specimens per individual host were 4.7 and 1309.7, respectively. The rich abundance of infection suggests a rich concentration of helminth intermediate/paratenic hosts in the coastal waters of Terra Nova Bay. Chionodraco hamatus serves as a definitive host for 10 helminth taxa, while it acts as an intermediate/paratenic host for 6 helminth taxa. Larvae of 6 helminth taxa for which C. hamatus serves as intermediate/paratenic host represented 98.7% of all specimens found. Of these, the tetraphyllidean and diphyllobothridean cestodes and the nematode Contracaecum osculatum s.l. were the most prevalent and abundant. 'Larval' infracommunities had significantly higher species richness, total abundance and diversity than 'adult' infracommunities, suggesting the important role of C. hamatus in supporting the life cycles of those parasites in the study area as a paratenic/intermediate host. Significant differences in the pattern of helminth infracommunities of larval forms between male and female fish were found. These differences could be caused by physiological, and most probably by behavioral differences between sexes suggesting that sex is an important factor influencing parasite burden in C. hamatus during reproductive season.